Road Safety Assessment Tool (RSAT) in determining level of safety for road design - Raja Nhari, Raja Nurulhaiza (2017)
In Malaysia, there is an absence of standard guideline to determine the level of safety at design stage road project and inadequate numbers of certified auditors that are qualified as Road Safety Auditor. This research aims to design questionnaire related to safety measures of road design and to identify the best constant obtained from the multiply factors. This research attempts to determine the level of safety for road design project. The survey is conducted among the road user to get the respondent opinion about the road safety issue base on the element of road design. From the data survey, the data were analysed using statistical tool to obtain multiply factor and Road Safety Assessment Tool (RSAT) were then developed to check level of safety for road design project based on the constant resulted from analysis.The RSAT gave recommendation base on the Level of Safety where result score more then 80% will recommend that the design road project can be proceeded and below than 80% is recommended to design reviewdue to unsafe or potential hazard to road user. It is believed that the results of this study could provide a model for local agencies nationwide to implement road safety audit recommendations more effectively. It can be concluded that RSAT can be one of the tools to facilitate the review of road safety audit report. RSAT will help practitioners but this was the first step for quantifying RSAT recommendations.